BIMBINGAN KONSELING ISLAM DENGAN TEKNIK BIBLIOTERAPI DALAM MENGATASI DEKADENSI KEIMANAN MAHASISWA DI SURABAYA (Jurusan Bimbingan dan Konseling Islam, 2014)
he study aims to determine the Process Guidance and CounselingIslam with bibliotherapy Techniques in Addressing Decadence All imanan Astudent in Surabaya, as well as the results of Guidance And Counseling Islamwith bibliotherapy Techniques in Addressing Decadence All imanan A student inSurabaya. The method used in this research is descriptive qualitative, whereasthe type of case study research. In this research, writer and counselor providesguidance and counseling Islam with measures of counseling that includes the step of problem identification, diagnosis, prognosis, treatment and evaluation. Having held counseling, this study considered quite successful. This is consistentwith a score of 60% which tegolong in category 60% - 65%. The success of thisresearch can be seen from the reduced indicators of the problem, namely the loss of 6 symptoms of decadence faith than ever that there are 10 symptoms.